Life-cycle Cost Approach for Management of Environmental Resources:A Primer - Reddy, V. Ratna (Springer, 2015)
This book demonstrates the application of Life-cycle Cost Approach (LCCA) in the management of infrastructure and other investment projects in the context of developing countries. The main goal is to identify potential opportunities for the adoption LCCA in developing countries, with the help of case studies and best practices. The editors observe that developing countries are plagued with poor and fluctuating service delivery which affords low or no priority for environmental protection. They seek to instill at the policy-making level an understanding of why life-cycle cost assessment is central to achieving the goals of sustainable development as well as sustainable service delivery and to influence the behavior of sector stakeholders.